Radiographic Measurements (Vertebral Heart Scale) Of Popular Breeds Of Dogs In India (Applied Biological Research, 2014)
The present study was conducted in 250 healthy dogs (120 females and 130  male) to assess vertebral heart size (VHS) in various the breeds and sex.  The radiographic measurements recorded were right lateral VHS, left lateral VHS, dorsoventral VHS and cardiothoracic ratio CTR. The mean  VHS established were RL (10.21 ± 0.10) LL (9.93 ± 0.14) and DV (10.09 ± 0.13) for Labrador, RL (10.24 ± 0.35) LL (10.03 ± 0.27) and DV (10.30 ± 0.42) for German Shepherd, RL (9.63 ± 0.23) LL (9.46 ± 0.39) and DV  (9.73 ± 0.35) for Indian Spitz, RL (10.09 ± 0.22) LL (9.53 ± 0.33) and DV  (10.03 ± 0.34) for Pug and RL (9.59 ± 0.31) LL (9.39 ± 0.45) and DV (9.42 ± 0.31) for non-descript native breeds. On RL and LL views, the Labrador  and German Shepherd had significantly higher and native non-descript  dogs had the lowest mean VHS measurements than other breeds. The findings reflect it is imperative to consider the breed and the side of  radiographic view during evaluation of heart size based on thoracic  radiographs.
Keywords: Breeds; dog; radiography; vertebral heart size